An Analysis of Regional Competitiveness in Uzbekistan (2015-2023): Trends, Drivers, and Policy Implications - Abdusalomov, Marufjon (THE INNOVATION ECONOMY, 2026)
This report presents a comprehensive analysis of the Regional Competitiveness Index (RCI) across Uzbekistan's regions from 2015 to 2023. Utilizing a composite index approach, the RCI measures regional strengths and weaknesses across four key sub-indices: Economic Performance, Education and Training, Infrastructure, and Labour Market Efficiency. The study identifies significant disparities in competitiveness, with Tashkent city consistently demonstrating superior performance, while many other regions exhibit varying development trajectories and, in some cases, declining trends. The analysis delves into the specific contributions of each sub-index and its underlying indicators, highlighting regions of particular strength and those requiring targeted intervention. The findings underscore the importance of a data-driven approach to regional development, emphasizing the need for tailored policy responses, continuous human capital investment, and infrastructure modernization to foster balanced and sustainable growth across Uzbekistan. The report concludes with actionable recommendations for enhancing regional competitiveness and outlines future applications of the RCI framework as a vital tool for strategic planning and performance monitoring.